Can DIPPR Database be Used for an Estimation of the Speed of Sound? A Case Study of Liquid Hydrocarbons - POSTNIKOV, Eugene B. (Archives of Acoustics, 2016)
The paper analyses a possibility of utilising the information which is contained in DIPPR database for a calculation of the speed of sound, which is absent there. As an example, liquid hydrocarbons are considered: n-hexane, 1-hexene, cyclohexane, cyclohexene, benzene, and 1-hexanols, as well as representatives of n-alkanes with various hydrocarbon chain lengths. It is shown that the Brelvi-O'Connell correlation for the reduced bulk modulus, supplied with the correlations for the internal pressure at the normal boiling temperature, results in the values having accuracy comparable with other DIPPR data for the region below the boiling point bounded by the values of the reduced density around $ρ_r≈ 3.5$. The source of errors originated from the Brelvi-O'Connell correlation for larger reduced densities is discussed.